The Influence of E-Marketing and Information System on University Image - Liem Gai Sin, Rizan Machmud, David P.E. Saerang, Agus S. Soegoto, Rudy S. Wenas, (Opción, 2019)
The aim of the study is to investigate the influence of e-marketing and information system on the university image via the Gesca PLS analysis tool. The results of this study provide empirical evidence that e-marketing and information systems have a significant effect on improving university image in the eyes of students. In conclusion, the information system could help improve the image of the university because the information system had the ability to convey a variety of positive information from the university which led to positive changes in its image.